Sentence comprehension: effectors and goals, self and others. An overview of experiments and implications for robotics - Borghi, Anna M.; Gianelli, Claudia; Scorolli, Claudia (Frontiers in Neurorobotics, 2010)
According to theories referring to embodied and grounded cognition (Barsalou, 2008), language comprehension encompasses an embodied simulation of actions. The neural underpinnings of this simulation could be found in wide neural circuits that involve canonical and mirror neurons (Rizzolatti et al., 1996). In keeping with this view, we review behavioural and kinematic studies conducted in our lab which help characterize the relationship existing between language and the motor system. Overall, our results reveal that the simulation evoked during sentence comprehension is fine-grained, primarily in its sensitivity to the different effectors we employ to perform actions. In addition, they suggest that linguistic comprehension also relies on the representation of actions in terms of goals and of the chains of motor acts necessary to accomplish them. Finally, they indicate that these goals are modulated by both the object features the sentence refers to as well as by social aspects such as the characteristics of the agents implied by sentences. We will discuss the implications of these studies for embodied robotics.